2005
DOI: 10.1055/s-2004-826143
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns of Sedation and Monitoring Practice during Endoscopy: Results of a Nationwide Survey in Switzerland

Abstract: The use of sedation in gastrointestinal endoscopy has markedly increased over the last 13 years and the use of electronic monitoring has become standard practice. A significant percentage of Swiss gastroenterologists report that they use propofol, mainly in a hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
1
16

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(135 citation statements)
references
References 15 publications
5
113
1
16
Order By: Relevance
“…Based on the findings of the present study, no specific trend was observed in the association between peak Pc,CO 2 and change in Pc,CO 2 with procedure duration, both a short and a longer procedure duration were associated with the peak Pc,CO 2 and change in Pc,CO 2 . The ability to effectively measure Pc,CO 2 is an important step in patient monitoring as diagnostic bronchoscopies are performed using routine sedation and also drugs, such as propofol, which are considered as general anaesthetics are being increasingly used also in the absence of a trained anaesthetist [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of the present study, no specific trend was observed in the association between peak Pc,CO 2 and change in Pc,CO 2 with procedure duration, both a short and a longer procedure duration were associated with the peak Pc,CO 2 and change in Pc,CO 2 . The ability to effectively measure Pc,CO 2 is an important step in patient monitoring as diagnostic bronchoscopies are performed using routine sedation and also drugs, such as propofol, which are considered as general anaesthetics are being increasingly used also in the absence of a trained anaesthetist [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional sedation with benzodiazepines and opioids is being replaced by the use of propofol (1), as a single agent or in combination with standard sedatives, due to its ultrashort onset of action, its short plasma half-life and the faster recovery from sedation (2). This property makes it the ideal agent for use in ambulatory endosocopy, as it reduces post procedure surveillance (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its rapid recovery profile, the use of propofol has increased for many endoscopic procedures over the last decade [10][11][12][13][14]. Propofol produces safe, effective, and well-tolerated sedation [15].…”
Section: Discussionmentioning
confidence: 99%